Peran Biomarker Saliva Dalam Penentuan Maturasi Skeletal - Heriandi, Alyah; Kusnoto, Joko (Jurnal Kedokteran Gigi Terpadu, 2025)
Introduction: Accurate assessment of skeletal maturation is essential in orthodontic treatment planning during the growth period. Conventional radiographic methods, though commonly used, involve ionizing radiation and subjective interpretation. Salivary biomarkers offer a promising non-invasive alternative. Objectives: This study aims to explore the potential of salivary biomarkers as indicators of skeletal maturation. Discussion: Skeletal maturation is commonly assessed using the Cervical Vertebral Maturation Stages (CVMS) method, which evaluateIntroduction: Accurate assessment of skeletal maturation is essential in orthodontic treatment planning during the growth period. Conventional radiographic methods, though commonly used, involve ionizing radiation and subjective interpretation. Salivary biomarkers offer a promising non-invasive alternative. Objectives: This study aims to explore the potential of salivary biomarkers as indicators of skeletal maturation. Discussion: Skeletal maturation is commonly assessed using the Cervical Vertebral Maturation Stages (CVMS) method, which evaluates morphological changes in cervical vertebrae C2, C3, and C4 on lateral cephalometric radiographs. Each CVMS stage corresponds to specific growth phases—pre-pubertal, pubertal, and post-pubertal. This review investigates the correlation of IGF-1, ALP, and DHEAS in saliva with these CVMS stages. Results: IGF-1 levels increase significantly during CVMS 3–4, aligning with the pubertal growth spurt. ALP levels peak at CVMS 3 and 5, indicating osteoblastic activity. DHEAS shows a progressive rise from CVMS 1 to 6, with significant elevations during the pubertal transition. Conclusion: IGF-1, ALP, and DHEAS in saliva are potential non-invasive biomarkers that correlate with CVMS and may improve the accuracy of skeletal maturation assessment for optimal orthodontic intervention timing.s morphological changes in cervical vertebrae C2, C3, and C4 on lateral cephalometric radiographs. Each CVMS stage corresponds to specific growth phases—pre-pubertal, pubertal, and post-pubertal. This review investigates the correlation of IGF-1, ALP, and DHEAS in saliva with these CVMS stages. Results: IGF-1 levels increase significantly during CVMS 3–4, aligning with the pubertal growth spurt. ALP levels peak at CVMS 3 and 5, indicating osteoblastic activity. DHEAS shows a progressive rise from CVMS 1 to 6, with significant elevations during the pubertal transition. Conclusion: IGF-1, ALP, and DHEAS in saliva are potential non-invasive biomarkers that correlate with CVMS and may improve the accuracy of skeletal maturation assessment for optimal orthodontic intervention timing.